Captives in Gray : The Civil War Prisons of the Union - Pickenpaugh, Roger (Book collections on Project MUSE., 2009)
Perhaps no topic is more heated, and the sources more tendentious, than that of Civil War prisons and the treatment of prisoners of war (POWs). Partisans of each side, then and now, have vilified the other for maltreatment of their POWs, while seeking to excuse their own distressing record of prisoner of war camp mismanagement, brutality, and incompetence. It is only recently that historians have turned their attention to this contentious topic in an attempt to sort the wheat of truth from the chaff of partisan rancor. Roger Pickenpaugh has previously studied a Union prison camp in careful deta.